Soil pollution by pesticides, problems and ways to solution their solution (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this work, the objects of study were the processes occurring in the environment under the influence of pesticides. The purpose of the work is to assess the environmental risk of using pesticides based on modern research in order to create a priorit list of pesticides for monitoring in the soil layer and surface waters.To achieve our goal, we used the following field experiments, mathematical modeling, and a laboratory method for determining the toxicity of pesticides for earthworms Eisenia foetida. The environmental risk assessment system we proposed consists of three stages.Stage one: calculation of the risks of acute/chronic toxicity of the pesticide for aquatic organisms and earthworms.Stage two: calculation of the aggregate risk of using a pesticide, taking into account bioaccumulation in the tissues of living organisms and compiling ratings of pesticides - environmental pollutants. Stage three: monitoring of rated pesticides in soils and surface waters.
Keywords: pesticide, ecology, soil, mathematical modeling, earthworm Eisenia foetida, bioaccumulation, monitoring